Conceptualizing the impact of information and communication technology on individual time and energy use. (June 2020) - Bieser, Jan C.T.; Hilty, Lorenz M.
Highlights: Conceptual framework of causal relationships between ICT, time, and energy use. Specification of ICT impacts on activity planning and execution. Discussion of direct and indirect energy impacts of ICT-induced changes of time use. Qualitative assessment of time and energy impacts of 'telecommuting'. Abstract: The energy requirements of everyday activities such as housework, travel or sleep differ considerably; hence, individual time use – the pattern of activities individuals perform during a day – is crucial for the energy consumption associated with lifestyles. Increasing use of information and communication technology (ICT) in everyday life changes individual time use and thus affects the associated energy requirements. ICT can have increasing or decreasing effects on energy use (e.g. it can reduce transport through virtual mobility or increase transport by creating the desire to travel to places seen on the Internet). Understanding the causal relationships between ICT, time, and energy use is essential to promote its desired impacts and prevent socially and environmentally unfavorable (unsustainable) ones. Despite various approaches to time use across disciplines, no consistent conceptual framework of the impact of ICT on time use and environmental impact exists so far. In this paper, we review existing literature on (1) ICT impacts on time use, and (2) environmental impacts of time use. Aiming to bridge differences across disciplines and methodological approaches, we develop a conceptual framework for systematically assessing the impact of ICT on time and energy use. The core of this framework is the categorization of ICT impacts on the relaxation of time and space constraints to activities, parallelization, fragmentation, substitution, avoidance, and delegation of activities, changes to the duration and manner of activities, changes to the process of activity planning, and generation of new ICT-based activities. In a broader systems perspective, these effects also trigger causal chains which can form feedback loops and thus change time-use patterns with some delay (systemic effects). Changes in time use affect direct energy requirements through the energy used to perform activities (e.g. in the form of electricity or fuels). Indirect energy requirements, the energy embedded in goods, only change if production of goods can be avoided (e.g. if telecommuting leads to fewer cars being purchased). The net energy impact of a given ICT use case depends on direct and indirect energy requirements of the activities performed before and after adoption of the use case. We demonstrate the application of the framework by qualitatively assessing time and energy use impacts of a frequently discussed ICT use case: telecommuting.